Determination of Chronic Post-Inguinal Herniorrhaphy Pain in a Setting in Rural Africa - Wismayer, Richard (Issues and Developments in Medicine and Medical Research Vol. 2, 2022)
Introduction: In Africa, inguinal hernia is a common surgical condition with an incidence of 175 inguinal hernias per 100,000 people each year. Pain that persists for at least a duration of 3 months postoperatively following repair of an inguinal hernia defines chronic groin pain. Chronic groin pain is a potentially incapacitating complication, presenting a therapeutic and diagnostic challenge to the surgeon. Objective: The objective of this study was to determine the prevalence of chronic groin pain in a group of patients in a hospital setting in rural Africa. Methodology: A descriptive retrospective study was carried out between 1st April 2008 to the 31st July 2012 on all patients \(≥\)15 years of age that underwent an inguinal hernia repair were eligible in this study. Data was retrieved from patients’ clinical notes and theatre log books on age, sex, recurrence of hernia and post-operative pain lasting at least 3 months. Data obtained in the interview questionnaire included duration of pain, pain at the operation site, type of postoperative analgesia and a physical examination to determine recurrence was performed in the surgical-out-patients clinic. Results: One hundred and fifty eight patients following repair of inguinal hernia using the modified Bassini technique were analysed. Mean age was 44.84 years. The male:female ratio was 3.65:1 with a male predominance. Chronic groin pain/discomfort was reported in 22(13.92%) and this pain/discomfort lasted for at least 3 months post-operatively. Conclusions: The low incidence of chronic groin pain in our study may be due to the majority of them being operated as elective procedures under local anaesthesia with routine identification of the ilioinguinal nerve. However, a study with a larger sample size and a longer follow up may be required to ascertain the true prevalence of chronic groin pain following inguinal hernia surgery in rural Africa.